The aftermath of debt surges - M. Ayhan Kose; Franziska Ohnsorge; Carmen M. Reinhart; Kenneth S. Rogoff (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Debt in emerging market and developing economies (EMDEs) is at its highest level in half a century. In about nine out of 10 EMDEs, debt is higher now than it was in 2010 and, in half of the EMDEs, debt is more than 30 percentage points of gross domestic product higher. Historically, elevated debt levels increased the incidence of debt distress, particularly in EMDEs and particularly when financial market conditions turned less benign. This paper reviews an encompassing menu of options that have, in the past, helped lower debt burdens. Specifically, it examines orthodox options (enhancing growth, fiscal consolidation, privatization, and wealth taxation) and heterodox options (inflation, financial repression, debt default and restructuring). The mix of feasible options depends on country characteristics and the type of debt. However, none of these options comes without political, economic, and social costs. Some options may ultimately be ineffective unless vigorously implemented. Policy reversals in difficult times have been common. The challenges associated with debt reduction raise questions of global governance, including to what extent advanced economies can cast their net wider to cushion prospective shocks to EMDEs.
Keywords: F62; F34; F44; E32; E63; H6; H63; 330; Debt restructuring; growth; inflation; fiscal consolidation; financial repression; wealth taxes